Development and validation of the Bowel Cleansing Impact Review (BOCLIR). Issue 2 (15th January 2013) - Doward, Lynda; Wilburn, Jeanette; McKenna, Stephen P; Leicester, Roger; Epstein, Owen; Hedley, Vicki; Korala, Sanjeeva; Twiss, James; Jones, Deborah; Geraint, Mike
Abstract : Objective: Acceptability and tolerability of bowel cleansers influence whether patients are able to complete the prescribed dose and, consequently, the quality of the cleansing achieved. No standardised means of assessing patients' experience of using bowel cleansing is currently available. The aim of the study was to develop the Bowel Cleansing Impact Review (BOCLIR) to assess patient response to bowel cleansing products. Design: Content was derived from qualitative interviews. Face and content validity were assessed via cognitive-debriefing interviews. Finally, patients completed the BOCLIR and a demographic questionnaire. Item response theory (Rasch analysis) was employed for item reduction and assessment of unidimensionality. Internal consistency and construct validity were also assessed. Results: Analysis of 40 interviews resulted in the production of three scales; patient satisfaction, symptomatic impact and activity limitations. Scales were designed to be used alone or together. 19 debriefing interviews demonstrated BOCLIR acceptability, relevance and ease of completion. The validation survey involved 166 patients (52% male, mean (SD) age 54.3 (15.2) years). After misfitting and redundant items were removed all scales fit the Rasch model confirming their unidimensionality. Cronbach's α-coefficients were high (0.77–0.94) indicating good internal consistency. Scores on the BOCLIR were related to patients' willingness to use the product in future and ease of drinking the full preparation (p<0.01 for each scale). Conclusions: The BOCLIR is a new measure consisting of three unidimensional scales (satisfaction, symptoms and activity limitations) with good psychometric and scaling properties. The BOCLIR will allow accurate assessment of patients' response to bowel cleansing preparations.